Influence of essential and non-essential amino acids on calcium oxalate crystallization - KIRAN YILDIRIM, BERÇEM; SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2010)
The investigation on the mechanism of nucleation and growth of crystals at organic-inorganic interfaces is crucial for understanding biological and physiological calcification processes such as the formation of urinary stones. The effects of five different amino acids on the crystallization of calcium oxalate have been investigated at pH 4.5 and 37 degrees C in aqueous solutions in the batch type crystallizer. The products were characterized by Scanning Electron Microscopy (SEM), Fourier Transfer Infrared Spectroscopy (FT/IR) and X-Ray diffraction (XRD) analysis. Crystal size distribution (CSD) and filtration rate measurements were done. In order to determine the adsorption characteristics of amino acids on the calcium oxalate crystal surfaces, zeta potential measurements were also done and discussed. The results indicate that in the presence of all investigated amino acids, calcium oxalate monohydrate (COM) crystals were preferentially produced, but the crystal morphology varied with amino acid types and concentrations. Various crystal morphologies such as elongated hexagonal, coffin or platy habits were observed. In the presence of all investigated amino acids, the calcium oxalate crystallized in a monohydrate form. Electrostatic/ionic interaction, different adsorption properties and special functional effects of amino acids led to find different crystal morphology. (C) 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: calcium oxalate; amino acids; zeta potential; crystal morphology; CRYSTAL-GROWTH; CARBOXYLIC-ACIDS; MONOHYDRATE; INHIBITION; DIHYDRATE